Absence of an association between HLA-DRB1*04 and rheumatoid arthritis in newly diagnosed cases from the community. Issue 7 (July 1993) - Thomson, W; Pepper, L; Payton, A; Carthy, D; Scott, D; Ollier, W; Silman, A; Symmons, D
Abstract : OBJECTIVES–To determine HLA-DR4 and DR1 allele frequencies in a series of patients with newly diagnosed early inflammatory arthritis. METHODS–HLA-DR1 and DR4 frequencies were determined by oligonucleotide typing of 208 patients classified as having either rheumatoid arthritis (RA) or undifferentiated inflammatory polyarthritis. RESULTS–The frequency of occurrence of DR4 in these patients with RA did not differ significantly from that in controls in the United Kingdom (42 v 37%). HLA-DR1 was increased in the group with inflammatory polyarthritis (25 v 18%). CONCLUSIONS–The frequency of DR4 is not increased in newly diagnosed community based patients with RA. This supports the hypothesis that DR4 is less important as a marker for susceptibility to RA than it is for disease persistence or severity.